2019
DOI: 10.1111/cgf.13596
|View full text |Cite
|
Sign up to set email alerts
|

MyEvents: A Personal Visual Analytics Approach for Mining Key Events and Knowledge Discovery in Support of Personal Reminiscence

Abstract: Reminiscence is an important aspect in our life. It preserves precious memories, allows us to form our own identities and encourages us to accept the past. Our work takes the advantage of modern sensor technologies to support reminiscence, enabling self‐monitoring of personal activities and individual movement in space and time on a daily basis. This paper presents MyEvents, a web‐based personal visual analytics platform designed for non‐computing experts, that allows for the collection of long‐term location a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
2
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 52 publications
0
2
0
Order By: Relevance
“…Although a high accuracy is often desired of machine learning models, the focus of many HCML papers is on explaining a model or creating models that respond to user preferences instead of emphasizing model quality. We thus found that only 18% of studies measured the accuracy of the model(s) (e.g., [EKC∗20; LXL∗18; PZDD19]). Of these, the measure of accuracy is often studied and derived from direct comparison to ground truth data [BAL∗15], or varied among study conditions [DLW∗17].…”
Section: Dimensions Of Analysismentioning
confidence: 99%
See 1 more Smart Citation
“…Although a high accuracy is often desired of machine learning models, the focus of many HCML papers is on explaining a model or creating models that respond to user preferences instead of emphasizing model quality. We thus found that only 18% of studies measured the accuracy of the model(s) (e.g., [EKC∗20; LXL∗18; PZDD19]). Of these, the measure of accuracy is often studied and derived from direct comparison to ground truth data [BAL∗15], or varied among study conditions [DLW∗17].…”
Section: Dimensions Of Analysismentioning
confidence: 99%
“…The predominant data types are multivariate data (e.g., [PNKC20; WMJ∗19; XMT∗20]); text (e.g., [ARO∗17; ESD∗19; LLL∗19]); and images (e.g., [CRH∗19; LSL∗17; SSSE20]). Only very few papers use other data types like videos (e.g., [KAY∗19]) or geo data (e.g., [PZDD19]).…”
Section: Dimensions Of Analysismentioning
confidence: 99%